PERAN UNESCO DALAM PEMBERANTASAN BUTA AKSARA DI INDONESIA TAHUN 2007-2012 - Ade Sahputra; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes the role of UNESCO in eradication of illiteracy in Indonesia, 2007-2012 (Case Study: Papua) Illiteracy is a problem that occurs in almost every country in the world. Illiteracy is also strongly related to poverty, backwardness and helplessness. In 2005, the illiterate population in Indonesia is still around 18.4 million people, which means a state with the 8th largest illiterate population in the world. The high level of illiteracy in Indonesia are caused by five main causes, namely the elementary school dropout , weighing geographical condition of Indonesia, the emergence of new illiterate, the influence of sociological factors, as well as the return of a person becoming illiterate sufferers.The research method used is a descriptive of qualitative research method about the facts. This research is an explanatory that describe about problem, indication, policies, and actions. In writing techniques, the author’s collect and collate data through library research from several sources like books, journals, articles, websites, the media and others. The author’s also use the concept of a role in view the case in this study.This research shows the role that UNESCO works in Indonesia has shown its role in providing assistance and programs in an effort to accelerate the eradication of illiteracy.programs include education for all and Literacy initiative for empowerment.UNESCO worked intensely to stop the growth of new literacy and support their liberation from illiteracy. UNESCO is involved with all parties in order to protect the public in educational attainment in Indonesia.Keywords: Illiteracy, Role, UNESCO,Education For All (EFA)